Electromyography in the four competitive swimming strokes: A systematic review - Martens, J.; Figueiredo, P.; Daly, D. (Journal of Electromyography and Kinesiology, 2015)
The aim of this paper is to give an overview on 50 years of research in electromyography in the four competitive swimming strokes (crawl, breaststroke, butterfly, and backstroke). A systematic search of the existing literature was conducted using the combined keywords "swimming" and "EMG" on studies published before August 2013, in the electronic databases PubMed, ISI Web of Knowledge, SPORT discus, Academic Search Elite, Embase, CINAHL and Cochrane Library. The quality of each publication was assessed by two independent reviewers using a custom made checklist. Frequency of topics, muscles studied, swimming activities, populations, types of equipment and data treatment were determined from all selected papers and, when possible, results were compared and contrasted. In the first 20 years of EMG studies in swimming, most papers were published as congress proceedings. The methodological quality was low. Crawl stroke was most often studied. There was no standardized manner of defining swimming phases, normalizing the data or of presenting the results. Furthermore, the variability around the mean muscle activation patterns is large which makes it difficult to define a single pattern applicable to all swimmers in any activity examined.